Finite element contact analysis of the hollow cylindrical roller bearings - Bayrak, Ramazan; Sagirli, Ahmet (YILDIZ TECHNICAL UNIV, 2024)
The Hollow Cylindrical Roller Bearings (HCRBs) have some important advantages over solid cylindrical roller bearings such as low weight, good lubrication capability and high bearing stiffness. Additionally, it's also known that maximum contact stress value between the roller and race is less in hollow cylindrical roller bearings compared to solid cylindrical roller bearings. In this paper, the effect of roller's hollow size in Hollow Cylindrical Roller Bearing under a radial load on the maximum contact stress value and contact stress distribution is studied by using finite element method. The maximum tangential tensile stress occurring on the inner surface of the hollow roller is also investigated. Moreover, the effect of the penetration amount, which is a critical parameter for a nonlinear contact problem such as roller-race contact, on the contact stress is taken into consideration, as well. It's seen from the results that tangential tensile stress on the inner surface of the hollow roller has an effect on the value of optimum hollow size. Besides, it is deduced from results that the penetration amount between the contacting surfaces have considerable influence on the contact stresses and it should be taken into consideration when analyzing the roller-race contact problem by using finite element method.
Keywords: Hollow Cylindrical Roller Bearing (HCRB); Penetration; Contact Analysis; Finite Element Method; LIFE; Engineering